2017
DOI: 10.1177/0951484817727130
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a health literate organization: Formative research results from healthcare organizations providing care for undeserved communities

Abstract: Background Integrating health literacy into primary care institutional policy and practice is critical to effective, patient centered health care. While attributes of health literate organizations have been proposed, approaches for strengthening them in healthcare systems with limited resources have not been fully detailed. Methods We conducted key informant interviews with individuals from 11 low resourced health care organizations serving uninsured, underinsured, and government-insured patients across Missou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 12 publications
3
41
0
1
Order By: Relevance
“…However, only three studies [40,80,98] reported "costs" as an outcome. Health organizations need resources and strategies to save staff time and costs [128]. It would be desirable to justify health literate interventions by linking them to saving staff time or reducing costs to convince more health organizations (including business-driven health organizations) to transform themselves to meet health literacy goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, only three studies [40,80,98] reported "costs" as an outcome. Health organizations need resources and strategies to save staff time and costs [128]. It would be desirable to justify health literate interventions by linking them to saving staff time or reducing costs to convince more health organizations (including business-driven health organizations) to transform themselves to meet health literacy goals.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these considerations, scholars and practitioners are used to deal with individual and organizational health literacy as unrelated issues (French & Hernandez, 2013), neglecting the interdependencies which exist among them (Rikard & McKinney, 2017). From this point of view, it is not surprising that little is known about the overall impacts of inadequate health literacy on both health services' quality and health outcomes (Adsul et al, 2017). In fact, the evidence supporting the effectiveness of the interventions intended to improve individual health literacy may be considered to be unreliable, since the role played by organizational health literacy in promoting patient involvement and in fostering the health care professionals' willingness to perform as enablers of the patients' sleeping resources is generally overlooked.…”
Section: Discussion: How To Avoid Value Co-destruction Through Healthmentioning
confidence: 99%
“…The main aim of OHL is to establish the promotion of HL in all structures and processes within organizations [18,23]. Improving OHL is likely to enable health care organizations to be adapted to the needs of patients [17], to strengthen patient satisfaction [24], to improve the quality of care [25], and to provide equal access to health care tailored to the capacities and competences of the general population [26]. By doing so, not only can certain groups of people (e.g., those with limited HL) benefit from OHL measures, but all stakeholders in a particular setting [27].…”
Section: Organizational Hlmentioning
confidence: 99%
“…Guides of health-literate organizations differ greatly in their scope and context of application [33]. Particularly in English-speaking countries, there are numerous guides available to strengthen OHL [23,25,29,32]. It seems that guides on organizational health promotion are mainly located in health care organizations (i.e., hospitals) [18,21,27].…”
Section: Measurement Of Ohl Interventions and Guidesmentioning
confidence: 99%
See 1 more Smart Citation